Biodiversity in fragmented key resource areas :Presistence of plant diversity and productivity in an intensely grazed key resource area - Skidmore, A.K. (University of Twente Faculty of Geo-Information and Earth Observation (ITC), 2020)
PhD thesis Univesity of Twente, Summary in English